2017
DOI: 10.1073/pnas.1619300114
|View full text |Cite
|
Sign up to set email alerts
|

CNS-resident progenitors direct the vascularization of neighboring tissues

Abstract: Organ growth requires the coordinated invasion and expansion of blood vessel networks directed by tissue-resident cells and morphogenetic cues. A striking example of this intercellular communication is the vascularization of the central nervous system (CNS), which is driven by neuronal progenitors, including neuroepithelial cells and radial glia. Although the importance of neuronal progenitors in vascular development within the CNS is well recognized, how these progenitors regulate the vasculature outside the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…In aggreement with previous studies (Miyata, 2017), we showed that the global as well as the local inhibition of Vegf signaling by overexpression of the Vegf decoy receptor sFlt1 led to a specific angiogenic phenotype, in which the hypophyseal capillary loop failed to connect properly to existing vessels. Such local effect of glial-derived Vegf signaling was recently demonstrated in the zebrafish spinal cord, where radial glia-derived Vegfab directed the formation of bilateral vertebral arteries and, subsequently, of the perineural vascular plexus in tissues adjacent to the spinal cord (Matsuoka et al, 2017). The idea that pituicyte-derived factors provide a pro-angiogenic microenvironment is also supported by reports that glial lesions of the neurohypophysis, dubbed pituicytomas, are highly vascularized, while another common pituitary tumor, adenomas, present less vascular density than the normal pituitary (Law-Ye et al, 2018).…”
Section: Pituicyte Regulation Of Vascular Morphogenesis and Permeabilitymentioning
confidence: 77%
“…In aggreement with previous studies (Miyata, 2017), we showed that the global as well as the local inhibition of Vegf signaling by overexpression of the Vegf decoy receptor sFlt1 led to a specific angiogenic phenotype, in which the hypophyseal capillary loop failed to connect properly to existing vessels. Such local effect of glial-derived Vegf signaling was recently demonstrated in the zebrafish spinal cord, where radial glia-derived Vegfab directed the formation of bilateral vertebral arteries and, subsequently, of the perineural vascular plexus in tissues adjacent to the spinal cord (Matsuoka et al, 2017). The idea that pituicyte-derived factors provide a pro-angiogenic microenvironment is also supported by reports that glial lesions of the neurohypophysis, dubbed pituicytomas, are highly vascularized, while another common pituitary tumor, adenomas, present less vascular density than the normal pituitary (Law-Ye et al, 2018).…”
Section: Pituicyte Regulation Of Vascular Morphogenesis and Permeabilitymentioning
confidence: 77%
“…All zebrafish husbandry was performed under standard conditions in accordance with institutional (MPG) and national ethical and animal welfare guidelines. Wild-type AB zebrafish and the previously established zebrafish lines Tg(kdrl:NLS-mCherry) is4 25 , TgBAC(cdh5:GAL4FF) mu101 26 , Tg(UAS:LIFEACT-GFP) mu271 27 , Tg(kdrl:EGFP) s843 28 , TgBAC(etv2:EGFP) ci1 29 , Tg(hsp70l:vegfaa 165 ,cryaa:cerulean) s712 30 , Tg(5xERE:GFP) c262 31 , kdrl hu5088 32 , flt1 bns29 33 , and vegfaa bns1 34 were used in this study. To improve readability, TgBAC(cdh5:GAL4FF); Tg(UAS:LIFEACT-GFP) was simplified to LIFEACT-GFP , and Tg(kdrl:NLS-mCherry) is referred to as NLS-mCherry .…”
Section: Methodsmentioning
confidence: 99%
“…Neurons in the central nervous system have high energy demands, and as such require robust vascularization for proper function (James and Mukouyama, 2011). During development, newly formed neurons and radial glia recruit and coordinate vascular formation in the spinal cord and neighboring tissues through the expression of genes such as vegfaa and flt1 (Matsuoka et al, 2017;Wild et al, 2017). Accordingly, during spinal cord regeneration, the vasculature must re-form properly in concert with CNS tissue.…”
Section: Angiogenesismentioning
confidence: 99%